The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph19042226
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Natural Outdoor Environment in Different Populations in Europe in Relation to Access: Implications for Policy

Abstract: This cross-cultural study explores the relationship of natural outdoor environment (NOE) use with NOE access. Most urban planning recommendations suggest optimal accessibility to be 300 m–500 m straight distance to spaces with vegetation of at least 1 hectare. Exploring this recommendation, we used data (n = 3947) from four European cities collected in the framework of the PHENOTYPE study: Barcelona (Spain), Doetinchem (The Netherlands), Kaunas (Lithuania) and Stoke-on-Trent (United Kingdom) to obtain resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…11 Moreover, where such evidence exists, there are indications that the development of and access to UGBS is not equitably distributed. 43,56 Two reviews 11,57 on UGBS in LMICs included the following recommendations:…”
Section: Ugbs In Lmic Settings: An Evolving Constructmentioning
confidence: 99%
“…11 Moreover, where such evidence exists, there are indications that the development of and access to UGBS is not equitably distributed. 43,56 Two reviews 11,57 on UGBS in LMICs included the following recommendations:…”
Section: Ugbs In Lmic Settings: An Evolving Constructmentioning
confidence: 99%
“…One of the most extensively researched links between urban park exposure and improved health and well-being outcomes is through increased physical activity [ 1 , 7 , 9 , 10 , 11 ]. Physical activity can protect against a range of diseases and adverse health outcomes, including cardiovascular disease, diabetes, cancer, hypertension, obesity, depression, osteoporosis, and premature death [ 12 , 13 , 14 , 15 ]. The World Health Organization (WHO) identifies physical inactivity as the fourth leading risk factor for global mortality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors influencing the intensity and frequency of park users engaging in physical activities include neighbourhood demographics, socio-economic conditions, park proximity, park size, park amenities, park programs, and perceived security [ 7 ]. Numerous studies have shown that proximity to parks and neighbourhoods with higher amounts of urban greenspace are positively associated with higher levels of engagement in physical activity [ 9 , 10 , 11 , 12 , 13 , 14 ]. A study by Villeneuve et al, examining recreational physical activities in Ottawa, Canada, based on neighbourhood greenness using a Google Street View greenness index, found that those living in areas scoring in the upper quartile on the index spent on average 5.4 more hours weekly on recreational physical activities relative to those in the lowest quartile [ 15 ].…”
Section: Introductionmentioning
confidence: 99%